Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12876-018-0799-6
|View full text |Cite
|
Sign up to set email alerts
|

Length of Barrett’s segment predicts failure of eradication in radiofrequency ablation for Barrett’s esophagus: a retrospective cohort study

Abstract: BackgroundWe aim to investigate factors that may contribute to failure of eradication of dysplastic Barrett’s Esophagus among patients undergoing radiofrequency ablation treatment.MethodsA retrospective review of patients undergoing radiofrequency ablation for treatment of Barrett’s Esophagus was performed. Data analyzed included patient demographics, medical history, length of Barrett’s Esophagus, number of radiofrequency ablation sessions, and histopathology. Subsets of patients achieving complete eradicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The length of Barrett's segment (greater than 5 cm) and number of RFA sessions (more than three) were significant predictors. 89 GERD, smoking, and male sex were also associated with incomplete CE-IM and CE-D; however, this was not significant. The association between more treatment sessions and failure of eradication may be explained by a more aggressive or invasive phenotype of disease.…”
Section: Surgery In Bementioning
confidence: 66%
See 1 more Smart Citation
“…The length of Barrett's segment (greater than 5 cm) and number of RFA sessions (more than three) were significant predictors. 89 GERD, smoking, and male sex were also associated with incomplete CE-IM and CE-D; however, this was not significant. The association between more treatment sessions and failure of eradication may be explained by a more aggressive or invasive phenotype of disease.…”
Section: Surgery In Bementioning
confidence: 66%
“…Luckett et al identified a number of factors associated with the failure of RFA (Table 1). 89 With RFA, 43% of patients failed to achieve CE-IM and 23.4% of patients failed to achieve CE-D, and 15.7% of patients were lost to follow-up and did not have posttreatment biopsies. The length of Barrett's segment (greater than 5 cm) and number of RFA sessions (more than three) were significant predictors.…”
Section: Surgery In Bementioning
confidence: 97%
“…Predictors of RFA failure are known to be length of BE segment, evidence of reflux, hiatus hernia length, race, duration of dysplasia and age. [35][36][37] Patients whose Barrett's esophagus is complicated with multifocal dysplasia, ulcerations and nodules are also likely to require more treatment sessions and therefore, may have a higher failure rate. However, numbers were too small in this cohort to investigate these factors further.…”
Section: Discussionmentioning
confidence: 99%
“…The response to ablation, the likelihood of achieving complete remission and the risk of recurrence have been shown to be less favorable in patients with ongoing esophagitis, long segment Barrett's, multifocal dysplasia, large hiatal hernia, and narrowed esophagus. [1][2][3] These considerations are kept in mind when approaching patients and discussing the risks benefits and alternatives to treatments.…”
Section: An Old Adage In Carpentry Is To Measure Thrice Check Twice A...mentioning
confidence: 99%